Evaluation of Leea rubra Leaf Extract for Oxidative Damage Protection and Antitumor and Antimicrobial Potential - Nibedita Das; Sanowar Hossain; Jaytirmoy Barmon; Shahnaj Parvin; Mahadi Hasan; Masuma Akter; Ekramul Islam (Journal of Tropical Medicine)
Background. The leaves of Leea rubra contain an abundance of phenolic constituents and have medicinal uses as antipyretic and diaphoretic agents and are also used in the treatment of stomach ache, rheumatism, arthritis etc. In spite of the traditional uses, data on the scientific evaluation of the plant are not sufficient. So, the present study was designed to evaluate the protective role of the extract against oxidative damage to DNA and human erythrocytes as well as antitumor and antibacterial activities against some resistant bacteria. Methods. The protective activity of the ethyl acetate fraction (EAF) of the extract was investigated by evaluating the inhibition of oxidative damage of pUC19 plasmid DNA as well as hemolysis and lipid peroxidation damage to human erythrocytes induced by 2,2′-azobis-2-amidinopropane (AAPH). Antitumor activity was assessed by evaluating the percentage inhibition of cell growth, morphological changes of Ehrlich’s ascites carcinoma (EAC) cells, and hematological parameters. Antimicrobial activity was determined by the disc diffusion method against different resistant microorganisms. Results. EAF effectively inhibited AAPH-induced oxidative damage to DNA because it can inhibit the transformation of the supercoiled form of plasmid DNA to open circular and further linear form. The oxidative hemolysis caused by AAPH in human erythrocytes was inhibited by EAF extract in a time-dependent manner, and the production of malondialdehyde (MDA) was significantly reduced, which indicates the prevention of lipid peroxidation. In antitumor assay, 76% growth of inhibition of EAC was observed compared with the control mice (p<0.05) at a dose of 100 mg/kg body weight. Antimicrobial activity was evaluated against two pathogenic resistant microorganisms (Escherichia coli and Pseudomonas aeruginosa), and the highest antimicrobial activity was observed against Pseudomonas spp. Conclusion. EAF may have great importance in preventing oxidative damage to DNA, erythrocytes, and other cellular components as well as can be a good candidate in cancer chemotherapy and treating infectious diseases caused by antibiotic-resistant bacteria.